2010
DOI: 10.1111/j.1755-5922.2009.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in High‐Risk Hypertensive Patients Treated with Beta‐Blockade Agents

Abstract: Background: Erectile dysfunction (ED) is a multifactorial disease related to age, vascular disease, psychological disorders, or medical treatments. Beta‐blockade agents are the recommended treatment for hypertensive patients with some specific organ damage but have been outlined as one of leading causes of drug‐related ED, although differences between beta‐blockade agents have not been assessed. Methods: Cross‐sectional and observational study of hypertensive male subjects treated with any beta‐blockade agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 37 publications
5
68
1
4
Order By: Relevance
“…For example, older age is also associated with an increased prevalence of comorbidities and polypharmacy, whereas younger age is a key determinant of poor therapy adherence [Briesacher et al 2008;Fischer et al 2010]. In addition, antihypertensive medication itself is independently associated with a higher risk of adverse events (AEs) such as erectile dysfunction (ED) [Cordero et al 2010;Düsing, 2005;Ko et al 2002;Shiri et al 2007] and orthostatic hypotension (OH) [Cleophas and van Marum, 2003], which may affect quality of life and lead to treatment discontinuation in both younger and older patients [Fogari and Zoppi, 2004]. Therefore, patient age should be carefully taken into consideration when selecting antihypertensive therapy [Carlberg and Nilsson, 2010].…”
mentioning
confidence: 99%
“…For example, older age is also associated with an increased prevalence of comorbidities and polypharmacy, whereas younger age is a key determinant of poor therapy adherence [Briesacher et al 2008;Fischer et al 2010]. In addition, antihypertensive medication itself is independently associated with a higher risk of adverse events (AEs) such as erectile dysfunction (ED) [Cordero et al 2010;Düsing, 2005;Ko et al 2002;Shiri et al 2007] and orthostatic hypotension (OH) [Cleophas and van Marum, 2003], which may affect quality of life and lead to treatment discontinuation in both younger and older patients [Fogari and Zoppi, 2004]. Therefore, patient age should be carefully taken into consideration when selecting antihypertensive therapy [Carlberg and Nilsson, 2010].…”
mentioning
confidence: 99%
“…21 In a recent report from a registry of hypertensive patients treated with a BB, we demonstrated that the use of different BBs differs if heart failure or CAD are present. 19 We did not find differences in BB doses between patients with RHR below or above 70 bpm, although the absence of dose equivalence should be addressed. Nevertheless, parameters like selectivity or vasodilator activity can be highly dosedependent, as different patients may exhibit widely variable pharmacodynamic responsiveness to the same dose of an individual drug.…”
Section: Discussionmentioning
confidence: 90%
“…18 In the DELTHA registry (DisfunciónErectiL en pacientes con HTA [Erectile Dysfunction in Hypertensive patients]), nebivolol was independently associated with lower prevalence of erectile dysfunction. 19 The largely debated meta-analysis by Lindholm et al 16 showed that BB treatment for hypertension was associated with lower or no cardiovascular protection compared to angiotensin-converting enzyme, angiotensinreceptor blockers, diuretics, or CCBs, but this effect was largely attributable to the results obtained in clinical trials with atenolol. More recently, another meta-analysis 37 addressed the negative effect of RHR reduction with BBs in patients with hypertension, especially driven by the effect of atenolol.…”
Section: Discussionmentioning
confidence: 99%
“…A large, cross-sectional study of more than a thousand middle-aged and older high-risk hypertensive patients reported the effects of betablockers on erectile function [50]. Erectile dysfunction was highly prevalent (71%) among users of beta blockers for at least 6 months and the dysfunction was of relatively high severity (16.1% severe; 16.8% moderate; and 38.1% mild).…”
Section: Nebivolol Versus the Other Beta Blockers In Hypertensive Patmentioning
confidence: 99%